Constrained crystallization of poly(L-lactic acid) in thin films prepared by dip coating. (April 2018) - Vayer, Marylène; Pineau, Alain; Warmont, Fabienne; Roulet, Marjorie; Sinturel, Christophe
Graphical abstract: Highlights: PLLA thin films were prepared by dip coating solutions. The thin films were investigated using AFM and GIXRD. Withdrawal at high speed led to amorphous films. Withdrawal at low speed led to partially crystallized films. The nature of solvent and molecular mass influenced the crystalline structure of the films. Abstract: Dip coating process used at various withdrawing speeds showed a great ability to control the crystalline structure of thin films of poly(L-lactic acid) which can be of great importance for applications where mechanical or optical properties are involved. Thin films were studied by Atomic Force Microscopy and Grazing Incidence Angle X-ray Diffraction. Withdrawing the silicon substrate in the draining regime (at high speeds) led to amorphous films with flat surface whatever the solvent and the molar mass. At low speeds (capillary regime), AFM demonstrated the presence of spherulites or hedrites in the films depending on the solvent and the molar mass. GIXRD showed that spherulites were less crystallized than hedrites. This difference was attributed to solvent evaporation rate.